Effect of atmospheric oxygen on the kinetic parameters of thermal degradation of pine branch particles. (March 2021) - Niu, Huichang; Liu, Naian; Ji, Dan
Abstract: Thermal degradation of forest combustibles plays an important role in the ignition and spread of wildland fires. Atmospheric oxygen affects thermal degradation mechanisms. In this paper, the thermal degradation behavior of pine branch (PB) particles of Pinus Sylvestris is investigated by using a thermogravimetric analyzer under inert and oxidative atmospheres. Results indicate that the thermal degradation process of PB particles in nitrogen differs from that in oxidative atmospheres, except for the initial stage from room temperature to 250 °C. Comparison between DTG and DSC curves under atmospheres with oxygen concentrations 5%–21% indicates that thermal degradation is promoted by increasing atmospheric oxygen. A unified scheme composed of four first-order reactions is used for kinetic analysis by simulating TG data with heating rates of 10, 15, 20, and 25 °C/min simultaneously. Kinetic parameters and reaction rate coefficients have been calculated based on multi-heating rate data, by the combined use of Genetic algorithm (GA) and nonlinear fitting algorithm. It is shown that the unified scheme is capable of capturing the characteristics of thermal degradation reactions under all heating rates and oxygen concentrations. It is found that the activation energies of four reactions first increase with oxygen concentration increasing from 0% to 15%, and then remain constant with oxygen concentration increasing from 15% to 21% except for reaction 2. The reaction rate coefficients of reactions 1, 3 and 4 obviously increase with oxygen concentration, while that of reaction 2 does not depend on oxygen concentration. Highlights: Thermal degradation of pine branch particles under different oxygen atmospheres is investigated. Kinetic study is conducted for thermal degradation of pine branch particles with a model-fitting method. Kinetic parameters and reaction rate coefficients have been calculated. Variation of reaction rate coefficients for different reactions with the increase of oxygen is discussed.